Human Resource Planning - Walker W. James (Mcgraw Hill Book Company, 1980)
Preface, Introduction, Managerial Concerns and Practices, The Environment of Human Resource Planning, Impementing Human Resource Planning: Staff Roles, Needs Forecasting, Linking Human Resource Planning with Strategic Planning, Forecasting Human Resource Needs, Forecasting Models and Applications, Work Analysis: A Basis for Planning, Performance Management, Improving Organizational Performance, Appraising Individual Performance, Compensation Planning, Career Management, Managing Careers: Policies and Systems, Management Succession and Development Planning, Defining Career Opportunities, Individual Career Planning, Conclusion, The Impact of Human Resource Planning, Bibliography, Name and Subject Index.
Preface, Introduction, Managerial Concerns and Practices, The Environment of Human Resource Planning, Impementing Human Resource Planning: Staff Roles, Needs Forecasting, Linking Human Resource Planning with Strategic Planning, Forecasting Human Resource Needs, Forecasting Models and Applications, Work Analysis: A Basis for Planning, Performance Management, Improving Organizational Performance, Appraising Individual Performance, Compensation Planning, Career Management, Managing Careers: Policies and Systems, Management Succession and Development Planning, Defining Career Opportunities, Individual Career Planning, Conclusion, The Impact of Human Resource Planning, Bibliography, Name and Subject Index.